2014
DOI: 10.7202/1035700ar
|View full text |Cite
|
Sign up to set email alerts
|

La culture numérique des jeunes professeurs des écoles peut-elle permettre de réduire l’écart entre natifs et immigrants du numérique ?

Abstract: Le décalage entre les pratiques numériques des élèves et celles de leurs professeurs est important et semble s’accentuer : les pratiques des jeunes tendent à être ludiques et communicationnelles, tandis que celles des enseignants reposent sur des compétences globales techniques (Baron et Bruillard, 2001). Nos résultats tendent à montrer qu’en France de futurs professeurs des écoles ont, à l’instar de leurs futurs élèves, des pratiques personnelles construites à partir de connaissances primaires liées à leur ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…e digital textual productions and images among prospective teachers are important. ese results are consistent with those of Poyet [6] which reveal that 90% of prospective teachers produce digital texts for their personal and professional work, while 83% of them produced images for personal use and 39% for professional objectives. Digital simulations are poorly used, with 25% of prospective teachers indicating that they produce digital simulations during preparations, and 12.5% of them indicated that their trainers use digital simulations as a pedagogical resource during training.…”
Section: E Nature Of the Resources Producedsupporting
confidence: 89%
See 3 more Smart Citations
“…e digital textual productions and images among prospective teachers are important. ese results are consistent with those of Poyet [6] which reveal that 90% of prospective teachers produce digital texts for their personal and professional work, while 83% of them produced images for personal use and 39% for professional objectives. Digital simulations are poorly used, with 25% of prospective teachers indicating that they produce digital simulations during preparations, and 12.5% of them indicated that their trainers use digital simulations as a pedagogical resource during training.…”
Section: E Nature Of the Resources Producedsupporting
confidence: 89%
“…ese results confirm those of Lefebvre and Fournier [26] who emphasized that prospective teachers tend to use Microsoft office tools to produce documents related to their studies. ey also confirm those highlighted by Poyet [6], by emphasizing that the majority of prospective teachers use a word processor, mainly Microsoft Word, to produce professional-looking writing and also personal correspondence.…”
Section: E Use Of Pedagogical Toolssupporting
confidence: 79%
See 2 more Smart Citations